TREE COMMUNITY STRUCTURE IN THE PARAK ECOSYSTEM IN TANJUNG RAYA, AGAM DISTRICT - Zainal Umar, Muhammad; Kardiman, Reki (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2023)
Parak is one of the transitional ecosystems from agricultural land and forests, it can also be called agroforestry. Parak agroforests produce a variety of forest products that are both for sale and for household needs including construction timber, firewood, and non-timber products such as fruit, forest vegetables and medicines. The purpose of this study was to determine the community structure of trees in the Parak ecosystem in Tanjung Raya District, Agam Regency. This type of descriptive research using field survey methods. Data collection was carried out at 4 locations by making 10 observation plots at each location in Tanjung Raya District, Agam Regency. At each location area a 20x20 plot is made to measure the trees contained in the plot. The results of this study obtained data that there were 31 species with a total of 959 individuals. The highest IVI value at location 1 Cinnamomum verum was 61.45. The highest IVI was at location 2 Myristica fragrans of 86.08. The highest IVI at location 3 Cinnamomum verum was 66.63 and at location 4 was obtained by Durio zibethinus of 56.44. The species diversity index (H') at location 1 was 2.29, at location 2 was 1.59, at location 3 was 1.68 and at location 4 was 2.78. While the overall obtained is 3.31. The species diversity index (H') at locations 1,2,3 and 4 belongs to the medium category, and overall belongs to the high category.